-3y+7(y+4)=-4

Simple and best practice solution for -3y+7(y+4)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y+7(y+4)=-4 equation:


Simplifying
-3y + 7(y + 4) = -4

Reorder the terms:
-3y + 7(4 + y) = -4
-3y + (4 * 7 + y * 7) = -4
-3y + (28 + 7y) = -4

Reorder the terms:
28 + -3y + 7y = -4

Combine like terms: -3y + 7y = 4y
28 + 4y = -4

Solving
28 + 4y = -4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 4y = -4 + -28

Combine like terms: 28 + -28 = 0
0 + 4y = -4 + -28
4y = -4 + -28

Combine like terms: -4 + -28 = -32
4y = -32

Divide each side by '4'.
y = -8

Simplifying
y = -8

See similar equations:

| 5x+5y=8y+8 | | 5v+2=8(v+1) | | -6v+2(v-7)=22 | | 2r^2+2=5r | | 20=2(x-4)+2x | | 1.5t-150=450 | | 5w+9=-31 | | 2r^4+46r^2-100=0 | | 2y+14x=0 | | 2(4X-9)=40 | | -3=6(v+2)-3v | | w+l-2.8l=4.3 | | f(3)=-2(3) | | 50h+100=x | | 4-x^2+16y^2=0 | | 2x^2-3=197 | | -3(2x-2)=45+3 | | 6x^3+21x^2-45x= | | 64=4xf | | 3x+19*5=2 | | 2(y-6)=12 | | (w)(w+2)=40 | | 10x^4-9x^3= | | b+23.19=38.72 | | 3y+4=x+14 | | e^3x=87 | | 5(3a+2)=12a+11 | | 25+x^2=225 | | (5w)*(5w+18)=-81 | | 0=x^3+64 | | -8+6n=-50 | | 7xv=28 |

Equations solver categories